Determinants and consequences of corporate social responsibility decoupling—Status quo and limitations of recent empirical quantitative research - Patrick Velte (Corporate Social Responsibility and Environmental Management, 2023)
This study reviews recent empirical quantitative research on firm- and country-related determinants of corporate social responsibility (CSR) decoupling and the consequences on firm value. Based on legitimacy theory and agency theory, top managers use CSR decoupling for self-impression management and stakeholder attraction. Our review indicates that low (high) corporate governance quality increases (decreases) CSR decoupling and it has negative financial consequences for firms. We identify major research gaps and stress research recommendations for future CSR decoupling studies. Solid measures of CSR decoupling should compare quantitative performance measures and qualitative descriptions on CSR reports on strategies and processes. There is a great need to include automated text analyses of sustainability reports for future research designs. Due to extended regulations on CSR reporting from an international perspective, CSR decoupling remains a hot topic for researchers, business practice, and standard setters.
Keywords: 650; corporate governance; CSR decoupling; CSR washing; greenwashing; legitimacy theory